NMR Studies of Some Inorganic Fluorides - Quail, John (My University, 1963)
The F19 NMR spectrum of SF4 at - 101° C has been assigned as an A2B2 type spectrum, rather than A2X2 as previously reported. Sulphur and boron isotope effects on F19 NMR spectra have been observed for the first time and a new silicon isotope effect has been measured. An expression has been derived for the shape of the spectrum of a nucleus of spin I = 1/2 spin-spin coupled to a nucleus of spin I = 3/2 which is undergoing quadrupole relaxation. The derived expression is used to interpret the F19 spectra of BF3 and Cl03F over a wide temperature range. A new compound, IOF5, has been prepared, and identified by means of its F19 NMR spectrum.
Keywords: NMR Studies; Inorganic Fluorides; isotope; chemistry